An Overview of Recent Developments in the Application of Antigen Displaying Vaccine Platforms: Hints for Future SARS-CoV-2 VLP Vaccines - Doddy Irawan Setyo Utomo; Hamizah Suhaimi; Nor Azila Muhammad Azami; Fazren Azmi; Mohd Cairul Iqbal Mohd Amin; Jian Xu (Vaccines, 2023)
Recently, a great effort has been devoted to studying attenuated and subunit vaccine development against SARS-CoV-2 since its outbreak in December 2019. It is known that diverse virus-like particles (VLPs) are extensively employed as carriers to display various antigenic and immunostimulatory cargo modules for vaccine development. Single or multiple antigens or antigenic domains such as the spike or nucleocapsid protein or their variants from SARS-CoV-2 could also be incorporated into VLPs via either a genetic or chemical display approach. Such antigen display platforms would help screen safer and more effective vaccine candidates capable of generating a strong immune response with or without adjuvant. This review aims to provide valuable insights for the future development of SARS-CoV-2 VLP vaccines by summarizing the latest updates and perspectives on the vaccine development of VLP platforms for genetic and chemical displaying antigens from SARS-CoV-2.